Fast pyrolysis of oil palm kernel shell in a fluidized bed reactor: The effect of pyrolysis temperature on the yields of pyrolysis products - Norizan, A. (Trans Tech Publications Ltd, 2014)
This study investigates the effect of pyrolysis temperature on the yields of char, organic compounds, water and gas. Fast pyrolysis was carried out in a fluidized bed reactor of 108 mm in internal diameter operated at 400, 450, 500 and 550 °C with nitrogen gas with flow rate of 25 L(NTP)/min. In specific the effect of temperature on the yields of known and unknown organics in bio-oil is discussed. For higher total organics, 500 ºC was favorable. But higher phenol and acetic acid yields, 450 ºC was preferable. The major organics include acetic acid, phenol and furfural. The minor ones include 2-methylphenol, 4-methylphenol, 4-methylnaphthalene, benzene, toluene and THF. © 2014 Trans Tech Publications, Switzerland.